An approach for seismic design in Malaysia following the principles of Eurocode 8 - Pappin, J. W. , Dr.; Yim, P. H. I.; Koo, C. H. R. (The Institution of Engineers, Malaysia, 2012)
Link to publisher’s homepage at http://www.myiem.org.my/